2008
DOI: 10.1111/j.1553-2712.2008.00203.x
|View full text |Cite
|
Sign up to set email alerts
|

Direct Comparison of the Diagnostic Accuracy of Fifty Protein Biological Markers of Pulmonary Embolism for Use in the Emergency Department

Abstract: Objectives: Pulmonary embolism (PE) is associated with abnormal concentrations of many proteins involved in inflammation, hemostasis, and vascular injury. The authors quantified the diagnostic accuracy of a battery of protein biological markers for the detection of PE in emergency department (ED) patients.Methods: A random and a consecutive sample of ED patients evaluated for PE were prospectively enrolled at two academic EDs between August 2005 and April 2006. A plasma sample was obtained at enrollment, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 12 publications
1
22
1
1
Order By: Relevance
“…Thus, it is likely for this reason that only 1 of the 50 candidate biomarkers 10 afforded an increase in specificity, while retaining 100% sensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is likely for this reason that only 1 of the 50 candidate biomarkers 10 afforded an increase in specificity, while retaining 100% sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…In an associated report of this study, we found that myeloperoxidase (MPO) and C-reactive protein (CRP) demonstrated high and nearly equivalent areas under the curve in a head-to-head receiver operating characteristic curve analysis of 50 potential biomarkers of PE. 10 The hypothesis of the present study was that a negative second screening test (either CRP or MPO), following a positive D-dimer, can effectively exclude PE with sensitivity equal to that of D-dimer alone, but with increased specificity, thereby potentially decreasing the rate of unnecessary pulmonary vascular imaging. Figure 1 summarizes our tandem testing strategy and hypothesis.…”
mentioning
confidence: 99%
“…However decreased CRP levels are still significantly higher in VTE patients, even months or years later, than controls, and because of that, this inflammatory marker is known as an independent predictor of the VTE risk [43,45,48,51]. Among fifty markers investigated, CRP and MPO were only inflammatory markers applicable for diagnosis of PTE, albeit it should be noted that D-dimer test has shown the best diagnostic value due to its high sensitivity [52,53]. Moreover, adjustment of CRP levels made the association between factor VII-activating protease and DVT, insignificant [54].…”
Section: Inflammation Sensitive Plasma Markersmentioning
confidence: 96%
“…5) sinkt die Sensitivität allerdings auf 70 % [138]. Nordenholz et al testeten bei Patienten mit einer Lungenembolie oder einer tiefen Beinvenenthrombose 50 weitere Biomarker und fanden, dass lediglich D-Dimere, CRP und die Myeloperoxidase (MPO) eine gewisse diagnostische Aussage für das Vorliegen einer Lungenembolie besitzen [140]. Bei einem Grenzwert von ≥ 500 ng/ml betrug die Sensitivität und Spezifität von D-Dimere für das Vorliegen einer Lungenembolie oder einer Venenthrombose 100 %, womit eine frühere Studie, die den gleichen Grenzwert untersuchte, bestätigt wurde [141].…”
Section: Interstitielle Lungenerkrankungenunclassified